1985
DOI: 10.1002/j.1460-2075.1985.tb03789.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the sucrose synthase gene on chromosome 9 of Zea mays L

Abstract: The structure of the shrunken gene of Zea mays encoding sucrose synthase (EC 2.4.1.13) was determined by (i) sequencing the transcription unit and ˜1.2 kb of 5′ ‐upstream sequences from a genomic clone, (ii) by sequencing a nearly full length cDNA clone and (iii) by determining the transcription start site by a combination of primer extension experiments with synthetic oligodeoxynucleotide primers and S1 mapping. The sucrose synthase gene is 5.4 kb long, of which 2746 bp are found in the mature mRNA. The gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
103
0

Year Published

1985
1985
1995
1995

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(107 citation statements)
references
References 50 publications
4
103
0
Order By: Relevance
“…The 5' untranslated leader sequence of ferritin mRNA confers the translational regulatory property to a heterologous gene in a transformation assay (13,14). Similarly, it may be possible to identify regions in the well-characterized Sh gene (27) that are responsible for the translational control of SS I transcripts during anaerobic stress. Another level of translational control is based on phosphorylation/dephosphorylation of a protein elongation factor 2, EF2, described in mammalian cells (21).…”
Section: Chase Of [35s]met With Unlabeled Methioninementioning
confidence: 99%
“…The 5' untranslated leader sequence of ferritin mRNA confers the translational regulatory property to a heterologous gene in a transformation assay (13,14). Similarly, it may be possible to identify regions in the well-characterized Sh gene (27) that are responsible for the translational control of SS I transcripts during anaerobic stress. Another level of translational control is based on phosphorylation/dephosphorylation of a protein elongation factor 2, EF2, described in mammalian cells (21).…”
Section: Chase Of [35s]met With Unlabeled Methioninementioning
confidence: 99%
“…), which catalyzes the reversible reaction UDP + sucrose^ UDP-glucose + D-fructose, was first characterized in wheat germ by Leloir and coworkers, who also detected its activity in a great variety of plant species and tissues (Cardini et al, 1955). Recent advances on the subject have focused, to some degree, on the maize enzyme, which is a tetramer composed of subunits of 92 kDa (Su and Preiss, 1978;Chourey, 1981;Werr et al, 1985). Two non-allelic variants of the enzyme have been characterized (Chourey, 1981;Echt and Chourey, 1985) and the corresponding genes [Sh and Sus (= Ss2 = Css)] have been identified, cloned and sequenced (Chourey and Nelson, 1976;Burr and Burr, 1981;Werr et al, 1985;McCarty etal., 1986;Springer et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…The second gene, Ss2 or Css, is also expressed in several tissues but its expression is less affected by anaerobiosis (McCarty et al, 1986a). The Shl gene has been cloned and its entire DNA sequence has been determined (Geiser et al, 1980;Sheldon et al, 1983;Werr et al, 1985;Zack et al, 1986). Based on the ability of Shl probes to select by hybridization mRNA corresponding to the Css gene (McCormick et al, 1982), Css genomic clones have been isolated and characterized by McCarty et al (1986a) who have also located the Css (Ss2) gene near the centromere of chromosome 9 of maize, 32 map units from the Shl locus (McCarty et al, 1986b).…”
Section: Introductionmentioning
confidence: 99%
“…Two genes encoding sucrose synthase (Shl and Ss2 or Css) have been described in maize (Chourey and Nelson, 1976;Chourey, 1981aChourey, , 1986McCormick et al, 1982) and the corresponding isozymes were shown to have partial antigenic identity and very similar kinetic properties in the sucrose-cleavage reaction (Echt and Chourey, 1985). Shl is the structural gene for the major endosperm form of the enzyme which is a homotetramer composed of subunits of 92 kDa (Su and Preiss, 1978;Chourey, 1981b;Werr et al, 1985). This gene is expressed in other tissues at low levéis that can be drastically increased in response to anaerobiosis (Springer et al, 1986).…”
Section: Introductionmentioning
confidence: 99%